Poland’s business cycle in the context of the world cycle - Polszakiewicz, Barbara (Ekonomia i Prawo. Economics and Law, 2009)
The analysis begins with a synthetic discussion of the current state of the business cycle theory. Three groups of current theories have been briefly discussed: the real business cycle theory, the Neoschumpeter theory and those formulated within the framework of the new Keynesian economy. A common belief that deviations of production and employment from so-called natural levels are caused by various kinds of shocks of a random nature, coexists with these theories. This belief is characteristic of representatives of the new classical economy and of monetarists. It was assumed in this article that proving the rhythmicallity of oscillations which occur in reality is a sine qua non condition for including them in the regularity of development. This rhythmicallity should express itself in a comparatively small differentiation of duration, i.e. the cycle period. After accepting a quite elaborate definition of a cycle, most justified from the theoretical point of view, its periods in American, German and Polish economies were analysed. A period was counted from the beginning of the phase of revival in one business cycle to the beginning of the phase of revival in the next one. A very close resemblance between the cycle course in Poland and the compared economies was found.